ANALISIS PERMINTAAN DAGING SAPI DI KABUPATEN JEMBER - Hidayatullah, Moch Herdi; Widjayanti, Fefi Nurdiana; Fauzi, Nurul Fathiah (Fakultas Ekonomi dan Bisnis, 2023)
The beef that consumers want is meat that suits the needs and desires of consumers so that the attributes inherent in beef are important for producers to pay attention to from the supply to the marketing process. This research aims to determine the factors that influence demand for beef in Jember Regency and to calculate the elasticity of beef in Jember Regency due to price, income and cross-elasticity of demand due to the price of chicken meat. This research is descriptive with locations at traditional markets in various sub-districts including Panti, Jelbuk, Silo, Ledokombo, Ambulu, Tempurejo, Sumberbaru, Kencong, Sumbersari, Kaliwates and Patrang sub-districts, Jember Regency, East Java Province. Sampling used the incidental sampling method with a total of 100 respondents. Data collection was carried out through observation, interviews and questionnaires among beef consumers in Jember Regency. Data analysis used multiple linear regression analysis using Eviews 9.0 software. From the research results it can be concluded that the price of beef, income, number of family members, and tastes have a significant influence on demand for beef, while the price of chicken meat and age do not have a significant influence on demand for beef in Jember Regency and the elasticity of demand for beef shows that price elasticity the demand for beef is 6.051298, meaning that the demand for beef is elastic. Meanwhile, the cross elasticity is -0.164605, which shows that chicken meat can be categorized as a substitute for beef.